Polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel and preparation method thereof
Through the preparation of polyvinyl alcohol/cellulose/MXene hydrophobic conductive hydrogels functionalized by polyethyleneimine, the shortcomings of existing hydrogels in mechanical, conductive and ion adsorption properties are solved, and high-performance hydrogel materials are achieved.
Patent Information
- Application Number
- CN202510083485.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing polyvinyl alcohol-polyvinylimide hydrogels are not ideal in terms of mechanical properties, conductive properties and ion adsorption properties.
A polyvinyl alcohol/cellulose/MXene hydrophobic conductive hydrogel was used to function polyethyleneimine. A single-layer MXene nanosheet was prepared by mixing lithium fluoride with MAX phase-Ti3AlC2 under acidic conditions. The polyvinyl alcohol and polyethyleneimine were then dispersed in deionized water. Finally, the cellulose and monolayer MXene nanosheets were added to a homogeneous viscous liquid under ultrasonic and stirring conditions to prepare a hydrophobic conductive hydrogel.
It realizes the high tensile properties, frost resistance, adhesion, conductivity, wear resistance, swelling, rheology and sensing properties of hydrogels, and has good ion adsorption properties, which are suitable for water treatment.
Smart Images

Figure CN119708544A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogels, and in particular to a polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel and a preparation method thereof. Background Art
[0002] Hydrogel is a gel that is interconnected into a network structure by high molecular substances. Since there are usually some hydrophilic groups on the hydrogel polymers, a large amount of water can be absorbed. This water is locked in the gel network structure to form a hydrogel.
[0003] Polyethyleneimide (PEI) is a water-soluble polyelectrolyte polymer with primary, secondary and tertiary amines, which can form a strong hydrogen bond network with PVA. Polyvinyl alcohol (PVA) hydrogel is widely used in biomedicine, food, agriculture and other fields due to its water solubility, chemical stability, biodegradability and biocompatibility. It has been widely used as a hydrogel material in the past 10 years.
[0004] The prior art CN102786642A discloses a nanocellulose / polyvinyl alcohol gel composite material. A large number of crosslinking agents, initiators and other chemical reagents are used in the preparation process of the material. The preparation process is difficult to control and is not green and environmentally friendly. In addition, the ionic conductivity performance of the composite material finally prepared is not mentioned.
[0005] The prior art CN113480781A discloses a graphene / nanocellulose / polyvinyl alcohol ternary composite aerogel and a preparation method thereof. The nanocellulose content in the graphene / nanocellulose / polyvinyl alcohol ternary composite aerogel is 15wt% to 50wt%, and the polyvinyl alcohol content is 5wt% to 10wt%, but the mechanical properties and ion adsorption performance of the obtained material are average.
[0006] In summary, the existing polyvinyl alcohol-polyethyleneimide hydrogels are not satisfactory in terms of mechanical properties, electrical conductivity and ion adsorption properties. Summary of the invention
[0007] In order to solve the problems mentioned in the above background technology, the present invention provides a polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel and a preparation method thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions: A polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel and a preparation method thereof, comprising the following steps: S1. Under acidic conditions, lithium fluoride and MAX phase-Ti3AlC2 are mixed and reacted to obtain a single-layer MXene nanosheet; S2. dispersing polyvinyl alcohol and polyethyleneimine in deionized water to prepare a homogeneous viscous liquid; S3. Add cellulose and monolayer MXene nanosheets into the homogeneous viscous liquid to react and obtain a hydrophobic conductive hydrogel.
[0009] Preferably, in step S1, the mass ratio of lithium fluoride to MAX phase-Ti3AlC2 is 3:(0.5-3).
[0010] Preferably, in S1, the acidic condition is an aqueous solution of hydrochloric acid, nitric acid, or sulfuric acid.
[0011] Preferably, in S1, the mixing reaction conditions are: stirring at 40-60° C. for 40-50 hours.
[0012] Preferably, in step S2, the mass ratio of polyvinyl alcohol, polyethyleneimine and deionized water is 2:(0.5-4):(5-15).
[0013] Preferably, in step S2, the conditions for dispersing in deionized water are: stirring at 80-90° C. for 20-40 min.
[0014] Preferably, in step S3, the mass ratio of cellulose, single-layer MXene nanosheets, and viscous liquid is 1:(1-5):(5-15).
[0015] Preferably, in step S3, the reaction conditions are: ultrasound for 5-15 min, stirring for 20-40 min.
[0016] The present invention also provides a polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel, which is prepared by the above method.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention first obtains a single-layer MXene nanosheet, then prepares polyvinyl alcohol and polyethyleneimine into a homogeneous viscous liquid, and finally modifies polyethyleneimine-polyvinyl alcohol with a single-layer MXene nanosheet and cellulose to obtain a hydrophobic conductive hydrogel. The preparation method is simple and has excellent tensile properties, frost resistance, adhesion, conductivity, wear resistance, swelling, rheological properties, sensing properties and biocompatibility.
[0018] 2. The hydrogel prepared by the present invention also has good ion adsorption performance, combined with its excellent hydrophobic property, and has great application potential in the field of water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is the state diagram of the hydrogel in the environmental tolerance test; Figure 2 is the state diagram of the hydrogel after thawing; Figure 3 This is a comparison of the hydrogel returning to its original shape after being twisted and pulled; Figure 4 This is a comparison chart of the hydrogel before and after adsorption of chloroform solution in water. DETAILED DESCRIPTION
[0020] Hereinafter, the present invention will be described in detail. Before describing, it should be understood that the terms used in this specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted according to the meaning and concept corresponding to the technical aspects of the present invention on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented here are only preferred examples for illustrative purposes and are not intended to limit the scope of the present invention, so that it should be understood that other equivalents or improvements can be obtained therefrom without departing from the spirit and scope of the present invention.
[0021] In this document, the terms "include", "including", "have", "contain" or any other similar terms are open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed in this document, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist). In addition, in this document, the interpretation of the terms "include", "including", "have", and "contain" should be considered to have been specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of".
[0022] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially secondary ranges defined by all integer values, and should be deemed to have specifically disclosed individual values such as 1, 2, 3, 4, 5, 6, 7, 8, etc. within the range. Unless otherwise specified, the above interpretation method applies to all contents of the entire present invention, regardless of whether the range is broad or not.
[0023] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0024] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0025] Among them, MAX phase—Ti3AlC2, 400 mesh, Jilin Yiyi Technology Co., Ltd.; Polyvinyl alcohol, Aladdin reagent, P434374; Polyethylenimine, Aladdin reagent, E107077; Cellulose, Aladdin reagent, C434461. Example 1
[0026] Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 1.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 1 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel.
[0027] The hydrogel prepared in this example was subjected to an environmental tolerance test. Figure 1 , Figure 2 As shown, the hydrogel was cut into small pieces ( Figure 1 : The hydrogel was cut into 15 mm × 10 mm × 5 mm pieces. Figure 2: The static hydrogel size is 80mm×10mm×5mm), heated to 90°C for 1h, and then continued to be frozen at -20°C. After 5 times of repeated freezing and thawing, a new shape is formed. It can be seen that the hydrogel can still maintain its original elasticity.
[0028] The hydrogel prepared in this example was subjected to a stretch-recovery performance test. Figure 3 As shown, after twisting and strongly stretching the hydrogel, it can reach 300% of the length of the hydrogel itself (from 50mm to 150mm). After stretching and deformation, it can recover to its original length, changing only from 50mm to 50±2mm, with almost no change, thus maintaining the stable performance of the hydrogel.
[0029] The hydrogel prepared in this example was tested for its ability to absorb organic solvents. Figure 4 As shown, the hydrogel was placed in 80 mL of chloroform aqueous solution (stained with Sudan III) for adsorption for 10 h. It can be observed that the red organic solvent was completely adsorbed, the hydrogel showed swelling, and the hydrogel strips showed a wavy swelling feeling. Example 2
[0030] Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 0.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 1 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel. Example 3
[0031] Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 3 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 1 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel. Example 4
[0032] Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 1.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 0.5 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel. Example 5
[0033] Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 1.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 2 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel. Example 6
[0034] Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 1.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 4 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel.
[0035] Comparative Example 1 Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 1.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 1 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 0 g of cellulose and the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel.
[0036] Comparative Example 2 Preparation of poly(vinyl alcohol) / cellulose / MXene hydrophobic conductive hydrogel functionalized with polyethyleneimine: S1. 3 g of lithium fluoride and 45 mL of 9 M hydrochloric acid were stirred for 15 min, 1.5 g of MAX phase-Ti3AlC2 solid powder was added to the above mixture, and stirred at 45 ° C for 48 h. After the reaction, it was repeatedly washed with deionized water and centrifuged to a pH value of more than 6, ultrasonicated and centrifuged to obtain a uniform dark green single-layer MXene nanosheet; S2. Dissolve 2 g of polyvinyl alcohol and 1 g of polyethyleneimine in 10 mL of deionized water, heat and stir at 85 ° C for 30 min to obtain a homogeneous viscous liquid, and cool to room temperature for use; S3. Add 1 g of cellulose and 0 g of the MXene nanosheets obtained in step S1 to the viscous liquid obtained in step S2, ultrasonicate for 10 min, stir for 30 min to mix them evenly, remove bubbles from the mixed solution, pour it into a mold, and store it in a refrigerator at -20°C to form a hydrogel.
[0037] Results and Testing Elongation at break: GB / T1040.1-2018, test conditions: 50mm / min; Ionic conductivity: The hydrogel was taken and the electrochemical workstation was used to measure the ionic conductivity of the hydrogel. 0 -10 5 The resistance of the hydrogel fiber was measured in the frequency range of Hz, and the conductivity was calculated according to the formula.
[0038] σ = L / RS where R is the resistance of the hydrogel, L is the distance between the two electrodes, S is the cross-sectional area of the hydrogel, and σ is the conductivity.
[0039] Ion adsorption performance: In order to evaluate the dye adsorption capacity of the hydrogel, the anionic dye Congo red (CR) and the cationic dye methylene blue (MB) were selected as model dyes. The hydrogel samples were placed in a beaker with 20 mL of different dye solutions. The initial pH value of the dye was about 6.5 and the adsorption equilibrium was reached at 20 °C for 2-3 h. Then, the supernatant was taken out and diluted, and 2 mL of the solution was taken to detect the remaining dye solution concentration using a UV spectrophotometer within a fixed wavelength range (Congo red 498 nm, methylene blue 662 nm).
[0040] Prepare 0.005, 0.010, 0.015, 0.020, and 0.030 mg / ml dye standard solutions respectively, and use a UV spectrophotometer to measure the absorbance and draw an absorbance standard curve. Substitute the absorbance value measured each time into the equation of the standard curve fitting to calculate the dye concentration in the remaining solution. The adsorption capacity and adsorption rate are calculated using the following formula:
[0041] Where: Qe is the adsorption capacity in mg / g; C0 is the initial concentration of the dye in mg / L; Ce is the concentration of the dye at equilibrium adsorption saturation in mg / L; V is the volume of the adsorption solution in L; m is the initial mass of the hydrogel; Water retention rate: The weight (g) change of the hydrogel at room temperature was measured for 28 days.
[0042] Water retention rate (%) = (M0 / M1) * 100% Where: M0: initial weight of hydrogel; M1: weight after 28 days.
[0043] The results are shown in Table 1.
[0044] Table 1
[0045] As can be seen from Table 1, the hydrogel prepared in the present invention has excellent performance in elongation at break, ion conductivity, ion adsorption performance and water retention rate.
[0046] By comparing Example 1 and Comparative Examples 1 and 2, it can be seen that cellulose and MXene nanosheets have an important influence on the performance of the hydrogel. Regardless of the lack of cellulose or MXene nanosheets, the performance of the hydrogel is reduced to varying degrees, but the simultaneous use of the two produces a synergistic enhancement effect.
[0047] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel, characterized in that: The steps include: S1. Under acidic conditions, lithium fluoride and MAX phase-Ti3AlC2 are mixed and reacted to obtain a single-layer MXene nanosheet; S2. dispersing polyvinyl alcohol and polyethyleneimine in deionized water to prepare a homogeneous viscous liquid; S3. Add cellulose and monolayer MXene nanosheets into the homogeneous viscous liquid to react and obtain a hydrophobic conductive hydrogel.
2. The method for preparing a polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In the step S1, the mass ratio of lithium fluoride to MAX phase-Ti3AlC2 is 3:(0.5-3).
3. The method for preparing a polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In S1, the acidic condition is an aqueous solution of hydrochloric acid, nitric acid, or sulfuric acid.
4. The method for preparing a polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In S1, the mixed reaction conditions are: stirring at 40-60° C. for 40-50 hours.
5. The method for preparing a polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In the step S2, the mass ratio of polyvinyl alcohol, polyethyleneimine and deionized water is 2: (0.5-4): (5-15).
6. The method for preparing a polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In the step S2, the conditions for dispersing in deionized water are: stirring at 80-90° C. for 20-40 minutes.
7. The method for preparing a polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In the step S3, the mass ratio of cellulose, single-layer MXene nanosheets, and viscous liquid is 1:(1-5):(5-15).
8. The method for preparing a polyethyleneimine functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel according to claim 1, characterized in that: In step S3, the reaction conditions are: ultrasonication for 5-15 min, and stirring for 20-40 min.
9. A polyethyleneimine-functionalized polyvinyl alcohol / cellulose / MXene hydrophobic conductive hydrogel, characterized in that: Prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
CNF-MXene-PEI high-strength and high-conductivity material as well as preparation method and application thereof
CN113817230A
MPAE conductive composite hydrogel as well as preparation method and application thereof
CN115232331A
Nanofiber reinforced conductive organic hydrogel and preparation method thereof
CN116925390A